IMPLEMENTASI IDEOLOGI PANCASILA DALAM KEHIDUPAN ERA DIGITAL - Salsabila Salsabila; Sariah Sariah; Chelsyla Alviona; Muhammad Rifki Iskandar (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
. Ideology is an idea, concept, or view of life held by a country. Pancasila as the ideology of the Indonesian state means that Pancasila is a teaching, idea, theory or knowledge that is believed to be true and is used as a way of life for the Indonesian people and is a guide in solving the problems faced by Indonesian society. . As stated in the Preamble to the 1945 Constitution of the Republic of Indonesia. Currently, we have entered an era where everything is digital. Digital is electronic technology that is capable of storing, generating and processing various data contained in two states, namely positive and negative. With this digital era, everyone can communicate more closely even though they are hindered by great geographical distances. The role of Pancasila is very important in this digital era to maintain the character of Indonesian society and the state. Implementation of the Pancasila ideology in this digital era can be done by utilizing social media as an intermediary to preserve the noble values ​​contained in Pancasila.